Development of a technique for DNA detection and identification of toxigenic strains of Clostridium botulinum types A, B, E by the Real-Time PCR method - D. S. Yanov; A. V. Kuznetsovskiy; M. I. Dubrovin; A. V. Mironin; N. V. Onuchina; A. V. Filippov (Вестник войск РХБ защиты, 2023)
Botulism is dangerous toxic infection caused by a toxin produced by the bacterium Clostridium botulinum. The mortality rate from botulism can reach 70% of all cases of illness in case of untimely initiation of treatment. The pathogenesis of botulism involves the damage to the central nervous system by a toxin produced by C. botulinum. Currently there are seven recognized antigenic types of this toxin. Botulinum toxin is included into the group of biological agents and it is one of the most likely agents to be used in a biological attack. Since botulinum neurotoxin is a complex nucleoprotein complex and the traces of DNA can be detected even in purified toxin preparations, we have elaborated a technique for detecting and identifying DNA of toxigenic strains of Clostridium botulinum types A, B, E, that cause human botulism in most cases. This technique is based on the the detection of residual amounts of this DNA in botulinum toxin using multiplex real-time polymerase chain reaction (PCR) assay with fluorescent hybridization detection. The main obstacle to development of a technique for the detection and identification of DNA of toxigenic strains is the high variability of the genes responsible for the synthesis of botulinum toxin. We have established a region of the gene with the lowest homology in all strains. This requirement is met by a fragment of the bont gene that encodes a light chain of a neurotoxin and is highly conserved in the strains of C. botulinum producing one type of toxin. The paper represents the results of the definition of analytical sensitivity and specific activity of the developed method. The specificity of the determination is 100%, the analytical sensitivity – 1×102 mc./ml. The method can be used to analyze food, samples of clinical materials and environmental samples suspected of being contaminated with toxigenic strains of C. botulinum.